2021 IEEE 21st International Conference on Software Quality, Reliability and Security (QRS) 2021
DOI: 10.1109/qrs54544.2021.00069
|View full text |Cite
|
Sign up to set email alerts
|

Confuzzion: A Java Virtual Machine Fuzzer for Type Confusion Vulnerabilities

Abstract: Current Java Virtual Machine (JVM) fuzzers aim at generating syntactically valid Java programs, without targeting any particular use of the standard Java library. While effective, such fuzzers fail to discover specific kinds of bugs or vulnerabilities, such as type confusion, that are related to the standard API usage. To deal with this issue, we introduce a mutation-based feedback-guided black-box JVM fuzzer, called CONFUZZION. CONFUZZION, as the name suggests, targets security-relevant object-oriented flaws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…One of their discoveries touches on a highly critical security vulnerability in Java 9 that allowed untrusted code to disable the Security Manager and elevate its privileges. Confuzzion [7] is another JVM fuzzer which is more generic in the sense that it allows the generation of programs that are not possible to generate with Classming or Classfuzz. Dean et al [18] demonstrated that there is a significant number of flaws in the Java language and in these two browsers supporting it.…”
Section: Java Securitymentioning
confidence: 99%
“…One of their discoveries touches on a highly critical security vulnerability in Java 9 that allowed untrusted code to disable the Security Manager and elevate its privileges. Confuzzion [7] is another JVM fuzzer which is more generic in the sense that it allows the generation of programs that are not possible to generate with Classming or Classfuzz. Dean et al [18] demonstrated that there is a significant number of flaws in the Java language and in these two browsers supporting it.…”
Section: Java Securitymentioning
confidence: 99%
“…Classfuzz [26] is a coverage-guided method on JVM compilers, it employs MCMC sampling to guide mutator selection. Confuzzion [18] introduces a mutational feedback-guided fuzzer on JVM for exposing the type of confusion vulnerabilities. It uses historical execution information to randomly select mutation methods to generate new test cases.…”
Section: Related Workmentioning
confidence: 99%
“…It first compiles each benign/vulnerable program, then perform code transformations in the bytecode version of the program such that it does not break the vulnerable code semantics. We perform this step using a modified version of CONFUZZION [14] (see Section IV-C). INTJECT then decompiles the resulting mutated code pair into a new benign/vulnerable source code pair.…”
Section: Intjectmentioning
confidence: 99%
“…3) Mutated Datasets: In this work, we propose the use of semantic-preserving program mutations to transform an original dataset into a rich and diverse one that allows to learn the vulnerability intent under varying contexts. To mutate the original dataset, we employ CONFUZZION [14]. Basically, CONFUZZION is a mutation-based feedback-guided black-box JVM fuzzer, which is focused on the type confusion vulnerabilities detection.…”
Section: Experimental Datasetsmentioning
confidence: 99%